2016
DOI: 10.1002/etc.3630
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary methylmercury on the dopaminergic system of adult fathead minnows and their offspring

Abstract: Mercury (Hg) is a ubiquitous environmental contaminant and potent neurotoxin, which may be transformed by bacteria in aquatic ecosystems to methylmercury (MeHg), an organic form which bioaccumulates and biomagnifies. Consequently, long-lived organisms at the top of the food web are at risk of dietary MeHg exposure, which can be actively transferred from mother to offspring. Exposure during neurodevelopment can lead to serious, irreversible neurological dysfunction, associated with a variety of cognitive and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 54 publications
1
25
1
Order By: Relevance
“…2,4,6-TCP might likely have inhibited GH secretion by acting at the level of hypothalamo-hypophysial axis. Moreover, brain amines also exert a control on the release of GH (Canosa et al 2007 ), and toxicants affect the secretion of monoamine oxidase (Bridges et al 2017 ). Thus, 2,4,6-TCP probably acts at the HPG level to inhibit GH secretion.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,6-TCP might likely have inhibited GH secretion by acting at the level of hypothalamo-hypophysial axis. Moreover, brain amines also exert a control on the release of GH (Canosa et al 2007 ), and toxicants affect the secretion of monoamine oxidase (Bridges et al 2017 ). Thus, 2,4,6-TCP probably acts at the HPG level to inhibit GH secretion.…”
Section: Discussionmentioning
confidence: 99%
“…We previously published companion studies showing a range of developmental effects in ELS fathead minnows (FHM) exposed to maternally transferred MeHg. Results showed WW egg Hg concentrations at the lower end of the reported range of concentrations (low treatment mean: 0.04–0.06 μg/g Hg) were sufficient to induce neurological effects. , …”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies exist, which link exposure to metals to neurodegenerative diseases in vertebrates. Parkinson’s disease (PD) is characterized by dopaminergic neuron loss in the midbrain from mitochondria-initiated oxidative stress, leading to changes in motor activity. Similarly, MeHg has also been shown to preferentially accumulate in the mitochondria of neurons within the CNS, leading to a cascade of biochemical changes which culminate in oxidative stress, neuronal degeneration, and altered neurotransmission. ,,,,, Changes in motor activity were observed in embryonic FHM following developmental exposure to maternally transferred MeHg. , Though studies on neurodegeneration have typically focused on the CNS, there is an emerging link between nervous system function and gut microbiota . Interestingly, intestinal microbes produce almost half of the body’s dopamine (DA) from dietary substrates, forming the basis for bidirectional communication between intestinal microbes and the CNS. , This relationship is known as the microbiome–gut–brain axis implying a role for enteric microbiota in brain function and neurodevelopment. ,, Recently, a link between altered gut microbiome and Parkinson’s disease (PD) has been established in humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In adults, these studies have shown that at levels less than 200 ppb, MeHg inhibits membrane adenosine deaminase, and results in mt2 gene induction in the brain but otherwise has minimal impact on other brain transcripts 7981 . Mid-range levels (between 720 to 5500 ppb) show significant Hg accumulation in the brain 82 , delayed hatching, and increased mortality 83 , and the induction of hyperactive behavior coupled with decreased levels of the neurotransmitters, serotonin and dopamine 84,85 . At high doses (10 – 13 ppm), studies show alterations in proteins associated with gap junctions and oxidative phosphorylation, large increases in mt2, and mitochondrial dysfunction 81,82,86 .…”
Section: Pathological Effects Of Heavy Metals On Fish Neurodevelopmentmentioning
confidence: 99%